STRATEGY OF ISLAMIC PHILANTHROPY MANAGEMENT FOR ECONOMIC EMPOWERMENT AT BMH GERAI PONOROGO USING SWOT APPROACH (International Journal of Islamic Business, 2022)
Based on the 2017 Zakat Outlook data from BAZNAS shows the great potential of Islamic philanthropy in economic empowerment. Among these Islamic philanthropic institutions, namely LAZ Baitul Maal Hidayatullah Ponorogo. This study aims to determine the management of Islamic philanthropy for economic empowerment and development strategies for economic empowerment programs at BMH Gerai Ponorogo using descriptive qualitative methods and data collection techniques through documentation, non-participant observation, and semi-structured interviews. Then analyzed using descriptive analysis methods and SWOT analysis. This research shows that Islamic philanthropic management for economic empowerment of BMH Gerai Ponorogo uses a special allocation from infaq funds and also shadaqah for the BMH Gerai Ponorogo economic empowerment program in the form of grants for business capital. Currently there are 2 main programs of economic empowerment, namely “Pesantren Berdaya” Catfish Cultivation, Shaleh Hidyatullah Children's Education Center, Sumoroto, Kab. Ponorogo and Oyster Mushroom Cultivation for Dai Tangguh in Kec. Parang, Kab, Magetan, East Java. In the aspect of Islamic economic empowerment materially in the form of capital and business assistance. Meanwhile, spiritually this economic empowerment program aims to support Islamic preaching on these two objects. For the economic empowerment strategy, it is seen in 3 aspects: enabling aspects (pre-program implementation), BMH Gerai Ponorogo conducted a survey and a feasibility test for the type of business. Then in the aspect of empowering (implementing) BMH Gerai Ponorogo also participates in mentoring and business assistance by controlling it regularly for 1-3 months. For limited guidance, apart from meetings, also through online media such as YouTube, WhatsApp, Facebook to provide direction/advice and consultation on program development. For the aspect of protecting (evaluation) BMH Ponorogo Gerai accommodates complaints and obstacles experienced and formulates solutions. Overall, the BMH Gerai Ponorogo economic empowerment program has major problems in human resources and competency in managing economic empowerment. Researchers recommend the provision of training or recruitment of special experts for the development of economic empowerment programs both intensively and extensively at the BMH Gerai Ponorogo.